2022
DOI: 10.1007/s11262-022-01928-2
|View full text |Cite
|
Sign up to set email alerts
|

A dominant internal gene cassette of high pathogenicity avian influenza H7N9 virus raised since 2018

Abstract: The zoonotic H7N9 avian influenza virus emerged with the H9N2-origin internal gene cassette. Previous studies have reported that genetic reassortments with H9N2 were common in the first five human H7N9 epidemic waves. However, our latest work found that the circulating high pathogenicity H7N9 virus has established a dominant internal gene cassette and has decreased the frequency of reassortment with H9N2 since 2018. This dominant cassette of H7N9 was distinct from the cocirculating H9N2, although they shared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The result of the HA MCC tree indicated that the sporadic cases of HP H7N9 in poultry had been generally reported in northern China since 2018 (Fig. 1 C), which was consistent with the previous findings [ 6 , 24 ]. The HP H7N9 has rarely been detected in southern and southwestern China since its fifth epidemic wave (vaccination started at the end of wave 5).…”
Section: Resultssupporting
confidence: 91%
“…The result of the HA MCC tree indicated that the sporadic cases of HP H7N9 in poultry had been generally reported in northern China since 2018 (Fig. 1 C), which was consistent with the previous findings [ 6 , 24 ]. The HP H7N9 has rarely been detected in southern and southwestern China since its fifth epidemic wave (vaccination started at the end of wave 5).…”
Section: Resultssupporting
confidence: 91%
“…The H7N9 virus is still occasionally detected in chickens [3]. Considering its high pathogenicity and the enormous damage to the poultry industry [27], the recurrence of the H7N9 avian in uenza epidemic is of wide concern and widespread worry in the public health sector [4,5,27]. In order to improve animal welfare, reduce economic losses, and decrease human infections, vaccination is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018 and 2019, it triggered several disease outbreaks among chickens and zoo birds in northern China [3]. Although no human infections with H7N9 in uenza have been reported in the past few years, several epidemiological surveys from 2016 to 2017 indicated that the H7N9 virus has caused great economic losses to the poultry industry and posed a signi cant threat to human health [4,5]. The Centers for Disease Control and Prevention In uenza Risk Assessment Tool classi es low pathogenic H7N9 viruses as moderate to high epidemic risk, exhibiting a high potential emergence and impact [6].…”
Section: Introductionmentioning
confidence: 99%